Analysis of Student Perception on Guidance and Counseling Management System Implementation - Nola Erpiana Fitri; Uman Suherman; Ibrahim Al Hakim (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
The research aims to analyze students' perception of the implementation of the Guidance and Counseling (GC) management system in schools, identify managerial gaps, and formulate recommendations for developing a digital-based system. Comprehensive GC services require systematic management, regulated through the integrated POAC (Planning, Organizing, Actuating, Controlling) functions. The method used is descriptive qualitative through a Focus Group Discussion (FGD) with 10 high school students. The results showed significant success in the Actuating (Implementation) function (high interaction comfort and quality of interpersonal relationships). However, a critical communication gap was found in the Planning function, where the majority of students (9 out of 10) were unaware that the need assessment was used as the basis for program development. Furthermore, a strong aspiration from students was found towards the digitalization of GC services to increase accessibility and transparency, especially in scheduling and online need assessment. The implication is that the GC management system needs to be enhanced by strengthening two-way communication and integrating digital technology as part of the System Support to achieve accountability and effectiveness.